Analisis Potensi Genangan Tsunami dan Penentuan Jalur Evakuasi Berbasis Sistem Informasi Geografis di Desa Daruba Pantai – Kabupaten Pulau Morotai - Mohammad Ridwan Lessy; Nurhalis Wahiddin; Jefry Bemba; Marwis Aswan (Jurnal Wilayah dan Lingkungan, 2021)
Tsunami is one of the catastrophic events that threatened coastal areas in Morotai Island Regency. This is partly because the location of the regency is among several active faults. Therefore, the study aims to analyze the tsunami inundation area and determine a tsunami evacuation route in Daruba Pantai Village, South Morotai District. This study begins with the preparation of a digital elevation model and is compiled with other related maps to produce the tsunami inundation area at the study site. The study results show that a tsunami can hit 176.65 ha, with the disastrous and dangerous category being 5.02% and 0.66%. Meanwhile, specifically for the Daruba Pantai Village area with an area of 60.59 ha, the disastrous and dangerous categories are 10.72% and 1.30%, and the safe category is 36.61% and secure 23.07%. Furthermore, the preparation of the evacuation route is based on the scenario that residents from each zone of both the Neighborhood Unit (RT) and Community Unit (RW) are directed to follow the evacuation path to move towards the temporary shelter point and towards the safety zone.